Palynological study of the genus Fagonia L. (Zygophyllaceae, Zygophylloideae) in Libya. - Taia, Wafaa; Ibrahim, Manaser; Hassan, Salem; Asker, Abdelbaset (Libyan Journal of Science &Technology, 2022)
The pollen morphology of twelve Fagonia L. taxa, representing nine species and three varieties, collected from different locations in Libya were subjected in this study and documented in detail using light microscopy (LM) and scanning electron microscopy (SEM). Pollen grains characters include shape (Polar axis, Equatorial axis), apertures type, colpus and pore length, colpus edge, and exine sculpture (surface) were studied and photographed. The obtained results revealed that palynological characters can help in the identification of the studied taxa. Polar axis, Equatorial axis, and pore length varied as well as within the studied taxa. The result of the ANOVA tests indicates that the colpus and pore lengths are significantly different within the studied taxa. An identification key, as well as clustering analyses, based on the results obtained, have been constructed. The results indicated that the pollen characters within the studied Fagonia ta